giải pt a) 3x+2/2 – 3x+1 = 5/3 +2x b) (x+1)(x+2)=(2-x)(x+2) c) x+5/x-5 – x-5/x+5 = 20/x²-25

giải pt
a) 3x+2/2 – 3x+1 = 5/3 +2x
b) (x+1)(x+2)=(2-x)(x+2)
c) x+5/x-5 – x-5/x+5 = 20/x²-25

0 bình luận về “giải pt a) 3x+2/2 – 3x+1 = 5/3 +2x b) (x+1)(x+2)=(2-x)(x+2) c) x+5/x-5 – x-5/x+5 = 20/x²-25”

  1. Đáp án:

     

    Giải thích các bước giải:

    `a)`

    `(3x+2)/2-(3x+1)/6=5/3 +2x`

    `<=> (3(3x+2)-(3x+1)/6=(10+2x.6)/6`

    `<=> (9x+6-3x-1)/6=(10+12x)/6`

    `=> 6x+5=10+12x`

    `<=> 5-10=12x-6x`

    `<=> 5=6x`

    `<=> x=-5/6`

    Vậy tập nghiệm của phương trình là `S={-5/6}`

    `b) (x+1)(x+2)=(2-x)(x+2)`

    `<=> (x+1)(x+2)-(2-x)(x+2)=0`

    `<=> (x+2)(x+2-2+x)=0`

    `<=> (x+2).2x=0`

    `<=>` \(\left[ \begin{array}{l}x+2=0\\2x=0\end{array} \right.\) `<=>`\(\left[ \begin{array}{l}x=-2\\x=0\end{array} \right.\) 

    Vậy tập nghiệm của phương trình là `S={-2;0}`

    `c) (x+5)/(x-5)-(x-5)/(x+5)=20/(x^2-25)`

    `ĐKXĐ : x ne +-5`

    `<=> ((x+5)^2-(x-5)^2)/(x^2-25)=20/(x^2-25)`

    `<=> (20x)/(x^2-25)=20/(x^2-25)`

    `=> 20x=20`

    `=> x=1“(TMĐK)`

    Vậy tập nghiệm của phương trình là `S={1}`

    Bình luận

Viết một bình luận